Risk-return preferences in the pension domain: are people able to choose? - M.C.J. van Rooij; Clemens J. M. Kool; H.M. Prast (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2005)
In this paper we investigate pension preferences and the effect of individual freedom of choice on risk taking in the context of pension arrangements based on a representative survey of about 1000 Dutch citizens. The attitude towards pension schemes and portfolio choices is explained by individual characteristics. Our main conclusions are the following. Risk aversion is domain dependent and highest in the pension domain. The vast majority of respondents is in favour of compulsory saving for retirement and favours a defined benefit pension system. If offered a combined defined benefit/defined contribution system, the majority of the respondents would like to have a guaranteed pension income of 70% or more of their net labour income. Self-assessed risk tolerance and financial expertise are important explanatory variables of pension system attitude. Respondents are on average conservative in their investment policy. If given investor autonomy, they are willing to change the composition of their retirement savings portfolio in response to their personal financial situation, general economic conditions, and expectations of financial markets. Respondents may be inconsistent in their preferences. Especially respondents who have chosen a relatively safe portfolio (less stock, more bonds) appear to prefer the retirement income streams of the median investment portfolio to their own portfolio choice. Finally, the average respondent considers himself financially unsophisticated, but is not very eager to take control of retirement savings investment when offered the possibility to increase expertise.
Keywords: 330; behavioural finance; risk tolerance; pension preferences; defined contribution schemes; freedom of choice; portfolio investment